Health care system in Sudan: review and analysis of strength, weakness, opportunity, and threats (SWOT analysis) - Ebrahim, Ebrahim Mohammed Abdullah; Ghebreab, Luam Ghebrehiwot; Abdalrheem, Tasneem Abdalgfar Alawad; Juni, Muhammad Hanafiah (Knowledge E, 2017)
Background: The Republic of the Sudan located in north-east of Africa and is considered to be a lower-middle income country. The country has well established healthcare system with many drawbacks mainly due to economic and managerial reasons followed by prolonged political instability and sanctions. Objective: The aim of this study is to give an insight over the health services system in Sudan and to analyze the strength, weakness, opportunities, and threats (SWOT). Materials and Methods: The search was done from two electronic databases: MEDLINE/Pubmed and from public search engines: Google Scholar and Google with key Search words used mainly as “Healthcare system in Sudan“. Additionally, SWOT analysis of healthcare system in Sudan was carried out based on the Roemer's model of health service system. Results: The Sudanese healthcare system was analyzed for different components of the system: The system in Sudan has full package of strategic plans and policies be it in a long term or short. Despite this there is poor implementation and organization along with frail health information system. The main external factors that drawback the system is the overall economic instability which resulted in cutting of the health expenditure. Conclusion: The Sudan is a rich country in terms of natural resources and population. Its health service system has strengths and weaknesses. It needs to build on its qualified human work force, stress on its well-designed short and long-term strategies on health care system and the partnership with external funding institutions, while overcoming the challenges on creating the proper health information system, economic support system and centralization of health service and professionals.